PERAN LEMBAGA KEUANGAN DALAM MENINGKATKAN PREKONOMIAN DAN KESEJAHTERAAN MASYARAKAT - Irsatus Solehah; Sinta Nur Emilia; Muhammad Nazaldholifun Nafsi; Maulidi Insan Kamil; Achmarul Fajar (PT. Hasba Edukasi Mandiri, 2026)
This research examines the role of financial institutions, both banks and non banks, in improving people's welfare in Indonesia. This research uses a qualitative type of research method using a literature study approach. This study investigates the crucial functions of financial institutions such as fund mobilization, funding allocation, asset transfer, liquidity provision, income relocation, and poverty reduction. In particular, the majority of people do not know about non-bank financial institutions and cannot access them. This suggests that there is still an imbalance in how money and profits are distributed in society. The findings of this study show that financial institutions play an important role in promoting financial inclusion, especially for low-income people and micro, small and medium enterprises (MSMEs). Factors driving the increased role of financial institutions include the growth in income of middle-class families and individuals, changes in industry and technology, the ability of small savers to access financial instruments, operational efficiencies gained by financial institutions by pooling resources, helping to reduce liquidity costs and the need for more inclusive financial services.